Evidences of zooplankton vertical migration in stocked and never-stocked alpine lakes in Gran Paradiso National Park (Italy) - Rocco Tiberti; Mattia Barbieri (Oceanological and Hydrobiological Studies, 2011)
Abstract Zooplankton vertical migration was described in four high altitude lakes in Gran Paradiso National Park (Northern Italy) during 2008 summertime. The authors succeeded in describing the vertical distribution of 6 species: diel vertical migrations were observed in the case of adult crustacean species (Cyclops gr. abyssorum, Arctodiaptomus alpinus and Daphnia gr. longispina), whereas the remaining rotifer species (Keratella quadrata, Polyarthra gr. dolichoptera and Synchaeta gr. stylata-pectinata) and naupliar stages of copepods did not undergo migrations. Migratory behavior of Daphnia gr. longispina and Cyclops gr. abyssorum was influenced by the size of individuals, especially larger individuals use to migrate deeper during the day compared to the smaller conspecific. This study provides new evidences of zooplankton vertical migration in never-stocked lakes and highlights the need to consider the zooplankton migration as result of multiple causal factors.